Attendance at iron deficiency anaemia clinic: audit of outcomes 5 years on. (27th March 2013) - Pengelly, S.; Fabricius, M.; McMenamin, D.; Wu, E.; Metzner, M.; Lewis, S. J.; Hosie, K. B.
Abstract Aim To determine the long‐term outcomes of patients in whom no initial cause for their anaemia is established. Method Six hundred and thirty‐nine patients presenting to an iron deficiency anaemia pathway were prospectively entered onto a database. Initial assessment included haematological review, coeliac screen, oesophagogastroduodenoscopy and colonic imaging as per British Society of Gastroenterology guidelines. A 5‐year audit of outcomes was undertaken using patient medical records and hospital laboratory databases. Results A diagnosis was found initially in 266 (42%) patients, with 124 (19%) having a gastrointestinal (GI) luminal neoplasm, 54 (8%) of which were malignant. Twelve patients had a nonluminal or non‐GI malignancy. Eighty‐eight (14%) had benign upper GI bleeding and 23 (4%) had coeliac disease. One hundred and forty‐three (22%) did not have confirmed iron deficiency anaemia on review of haematinics. Complete records were available for 595 (93%) patients at 5 years. Of the 373 patients in whom a cause was not initially diagnosed, 6 (2%) were ultimately diagnosed with a GI luminal malignancy and 18 (5%) with a nonluminal or non‐GI malignancy. There was no difference in the incidence of malignancies between those with or without confirmed iron deficiency. Conclusions Most patients in whom no cause was found at initial investigation resolve on oral iron supplements. Patients with normal ferritin values had as high an incidence of GI malignancies as those with low values and should be investigated. In the over 50s if the anaemia remains after a course of iron further investigation is recommended as there is a significant incidence of both GI and non‐GI pathology.